Assessment of ion transfer amperometry at liquid–liquid interfaces for detection in CE - Sisk, G.; Herzog, G.; Glennon, J.; Arrigan, Damien (Wiley-VCH Verlag, 2009)
In this research, ion transfer across the interface between two immiscible electrolytesolutions (ITIES) was used as a method of detection in a CE separation system. Thismethod allows for the electrochemical detection of ionic analytes that cannot be easilyoxidized or reduced. Method development revealed that the optimal separation conditionsfor three model ions (tetraethylammonium, tetrabutylammonium, and benzensulfonate)were found to be 5mM sodium tetraborate buffer pH 9.2 with a separationvoltage of 20 kV using a 40 cm, 50 mm id fused silica capillary. Constant potentialamperometry and pulsed amperometric detection were applied at the ITIES in which theorganic phase was gelled. A miniaturized ITIES within a pipette tip was investigated,which resulted in improved separation efficiency and LOD. To demonstrate the ability ofthe system to detect substances of bioanalytical interest, the b-adrenergic receptorblockers timolol and propranolol were detected. The simplicity of the detection platformmeans that it may be useful for analytical situations not requiring trace or ultratracedetection capabilities.